1995
DOI: 10.1111/j.1600-0609.1995.tb00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased peripheral blood normal myeloid progenitor cells (CFU‐GM) in chronic lymphocytic leukemia: A perspective for autologous peripheral blood stem cell transplantation

Abstract: We assayed granulocyte‐macrophage committed progenitor cells (CFU‐GM) in the peripheral blood of 34 patients with chronic lymphocytic leukemia (CLL) and 12 normal individuals. The patients were divided into separate groups on the basis of previous therapy (i.e. analysis performed at diagnosis, during and after chemotherapy) and clinical features of the disease (i.e. disease stage, pattern of bone marrow infiltration, peripheral blood lymphocytosis). The mean CFU‐GM colony count of the patients was 30 times hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In the light of these more aggressive and potentially eradicating procedures, the biological features o€ the residual stem cell compartment in CLL has been marker of investigation. Tsatalas et al (6) reported an increased number of circulating Table 7 Haemopoietic PB (a) and BM (b) progenitors before and after cyclophosphamide and G-CSF in the 2 patients who failed stem cell mobilization CFU-GM in the PB of CLL patients at diagnosis and during or after therapy, making these patients candidates for autologous PB stem cell transplantation and suggesting the feasibility of autografting procedures even in patients who have undergone previous extensive chemotherapy and/or might have persistent BM infiltration. A different conclusion was reached in another report (7) in which the finding of an increased number of PB CFU-GM was not confirmed, although the study was conducted in a limited number of CLL patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of these more aggressive and potentially eradicating procedures, the biological features o€ the residual stem cell compartment in CLL has been marker of investigation. Tsatalas et al (6) reported an increased number of circulating Table 7 Haemopoietic PB (a) and BM (b) progenitors before and after cyclophosphamide and G-CSF in the 2 patients who failed stem cell mobilization CFU-GM in the PB of CLL patients at diagnosis and during or after therapy, making these patients candidates for autologous PB stem cell transplantation and suggesting the feasibility of autografting procedures even in patients who have undergone previous extensive chemotherapy and/or might have persistent BM infiltration. A different conclusion was reached in another report (7) in which the finding of an increased number of PB CFU-GM was not confirmed, although the study was conducted in a limited number of CLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known on the residual stem cell compartment in CLL and the few published reports have given contradicting results. Tsatalas et al (6) have recently reported an increased number of haematopoietic progenitors in the peripheral blood (PB) of untreated and treated CLL patients; this has not been confirmed in another study (7), in which a number of CFU-GM similar to that of healthy donors was recorded in untreated patients.…”
mentioning
confidence: 91%